FURTHER IMPROVEMENT OF ELECTRONIC MONEY REGULATION SYSTEM (World Bulletin of Management and Law, 2023)
This article is devoted to the analysis of issues such as the formation of a system of working with electronic money and improving the effectiveness of legal regulation in the conditions of a rapidly developing economy
Keywords: electronic money; cryptocurrency; issuer; legal provision